Evaluasi Keberlanjutan Sistem Pengelolaan Air Limbah Domestik Terpusat Skala Komunal - Abraham Abraham; Suharyanto Suharyanto (Journal on Education, 2023)
In previous research, several Communal SPALD-T/IPAL at SANIMAS Cimahi city were still in a less sustainable status in terms of financing, technical and social aspects. One of them occurred in the SANIMAS RW 10 and 16 Kelurahan Cibabat program which had problems with technical SOPs, community participation and difficult access. While in SANIMAS RW 19 there were problems with the management organization sector that was not optimal. With management conditions like this, challenges in management have also increased because the Indonesian government has implemented various "lockdown" restriction policies to prevent the spread of COVID-19 which has had quite a large impact on the city of Cimahi in 2020-2021. The RAPFISH assessment method (RAPWastman) is used by researchers to analyze each aspect of sustainability multidimensionally based on various indicators and provide a percentage value for the level of sustainability. The results of the analysis are then combined with a quantitative SWOT analysis as a tool to formulate a strategy for handling or developing SANIMAS. Based on the assessment of the results of the analysis, the sustainability of SANIMAS in the technical aspect is at the moderate to sustainable level (69%-81%), in the financing aspect is at the sufficient to sustainable level (59%-76%), in the environmental aspect at the sustainable level (78%-81 %), on the institutional aspect at the moderate to sustainable level (72%-87%), and on the social aspect at the moderate to sustainable level (67%-76%). The general strategy for optimizing the management of SANIMAS RW 10, 16 and RW 19 is to maximize the application of SOPs, access to spare parts, community involvement and assistance or training facilities from the government to maximize service quality and sustainability of SANIMAS management from various aspects.